Electromagnetic transients in large HV cable networks : modeling and calculations - Ametani, Akihiro; Xue, Haoyan; Ohno, Teruo; Khalilnezhad, Hossein (Institution of Engineering and Technology, 2021)
This book presents an overview of formulas to model transients in cable systems based on complete solutions of Maxwell's equations. It presents solutions to particularly model important high frequency phenomena. The impedance and admittance at a very low frequency for HVDC systems are investigated
Keywords: Transients (Electricity); Electromagnetism.; Electric cables.; High voltages.; elektronické knihy; electronic books